Separation of human erythrocyte membrane associated proteins with one-dimensional and two-dimensional gel electrophoresis followed by identification with matrix-assisted laser desorption/ionization-time of flight mass spectrometry - Low, T.Y. (2014)
10.1002/1615-9861(200209)2:93.0.CO;2-N